Estudo das patologias em concreto armado: estudo de caso edifício centro cultural São Paulo - Maehara, Renata Harumi [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This work presents a study of the pathologies in reinforced concrete of the São Paulo Cultural Center building (CCSP), located in São Paulo - SP. Its construction counted on approximately two thousand workers, a construction siteof three hundred metersand its built area of 46,500 square meters. Approximately 20 thousand cubic meters of reinforced concrete and approximately 2000 tons of steel were consumed (CENNI, 1991). The study of the pathologies of a building is important because it presents the most recurrent deteriorations, and the analysis of its causes, so that these are avoided in the future. The present work sought to present, through a case study, an initial, visual analysis of a study of pathologies addressing their causes and their characteristics. Information about the study object Centro Cultural São Paulo was carried out mainly in academic works related to it. Later, through site visits, visual inspections and accounting of the same were made. Based on information collected from the bibliographical survey, analyzes, quantification and hypotheses about the pathologies found on two floors of the São Paulo Cultural Center were carried out, in order to determine the most frequent in the building and the factors that led to its emergence. Through visual verification, it was possible to identify the most recurrent ones being: wear on abrasion, disaggregation, segregation, carbonation and corrosion. After the analysis of the pathologies, an evaluation of its causes was made, and the infiltrations in the coverage were the most significant for the work, because this influence directly the pathological manifestations presented.

Este trabalho apresenta um estudo das patologias em concreto armado do edifício Centro Cultural São Paulo (CCSP), localizado em São Paulo - SP.A sua construção contou com aproximadamente dois mil operários, um canteiro de mais de trezentos metros e sua área construída de 46.500 metros quadrados. Foram consumidos aproximadamente 20 mil metros cúbicos de concreto armado e cerca de 2.000 toneladas de aço (CENNI, 1991).O estudo das patologias de uma edificação se faz importante por apresentar as deteriorações mais recorrentes, e a análise de suas causas, de forma que estas sejam evitadas futuramente. O presente trabalho procurou apresentar,através de um estudo de caso, uma análise inicial, visual, de um estudo de patologias abordando suas causas e suas características. Foi feita o levantamento de informações sobre o objeto de estudo Centro Cultural São Paulo principalmente em trabalhos acadêmicos relacionados a ele. Posteriormente, através de visitas ao local, foram feitas as inspeções visuais e contabilização das mesmas. A partir de informações retiradas do levantamento bibliográfico, foram feitas as análises, a quantificação e hipóteses sobre as patologias encontradas em dois pisos do Centro Cultural São Paulo, de forma a determinar as mais frequêntes na edificação e os fatores que propiciaram seus surgimentos. Mediante verificação visual, foi possível identificar-se as mais recorrentes sendo elas: desgaste à abrasão, desagregação, segregação, carbonatação e corrosão. Após a análise das patologias, foi feita uma avaliação de suas causas, sendo as infiltrações na cobertura a mais significativa para o trabalho, pois esta influenciou diretamente as manifestações patológicas apresentadas
Study of pathologies in reinforced concrete: case study building cultural center São Paulo
Keywords: Patologia de construção; Edifícios - Deterioração; Concreto armado; Construção civil; Reinforced concrete